Prime Minister's office: the Fulcrum of Indian administration - Jha, Rajani Ranjan (2019)
Prime minister occupies a pivotal position in any parliamentary system of government. At the time of India$1 (Bs Independence, the prime minister$1 (Bs office (PMO) started working as a low profile non-constitutional and non-statutory body. But within less than two decades, the PMO emerged as an institution with a formidable influence in policymaking. It was sometimes labelled as the parallel government. This article is a modest attempt to discuss the origin and development of the PMO in India right from Prime Minister Jawaharlal Nehru to PM Narendra Modi. In the process, it deals briefly with the organisational structure of PMO and the role of the principal secretary to the PMO. Additionally, the article examines how with every prime minister importance of the PMO changes. This nerve centre of power basks in the reflected glory of its incumbent, the Prime Minister of India. - Reproduced.s
Keywords: Prime Ministers Office; Public administration; Parliamentary systems